Quantitative characterization of the lipid encapsulation of quantum dots for biomedical applications - Galloway, Justin F.; Winter, Alan; Lee, Kwan Hyi; Park, Jea Ho; Dvoracek, Charlene M.; Devreotes, Peter; Searson, Peter C. (ELSEVIER, 2012)
The water solubilization of nanoparticles is key for many applications in biomedicine. Despite the importance of surface functionalization, progress has been largely empirical and very few systematic studies have been performed. Here we report on the water solubilization of quantum dots using lipid encapsulation. We systematically evaluate the monodispersity, zeta potential, stability, and quantum yield for quantum dots encapsulated with single and double acyl-chain lipids, pegylated double acyl-chain lipids, and single alkyl-chain surfactant molecules with charged head groups. We show that charged surfactants and pegylated lipids are important to obtain monodisperse suspensions with high yield and excellent long-term stability. From the Clinical Editor: This study reports on solubilization of nanoparticles in water, a key, but often neglected aspect for biomedical applications. The authors demonstrate that charged surfactants and PEGylated lipids are important to obtain monodisperse suspensions with high yield and long-term stability. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: PHOSPHOLIPID MICELLES; NANOCRYSTALS